The cost‐effectiveness of immediate treatment or watch and wait with deferred chemotherapy for advanced asymptomatic follicular lymphoma. (26th October 2017) - Prettyjohns, Matthew; Hoskin, Peter; McNamara, Christopher; Linch, David
Summary: Recent evidence has shown that immediate treatment with rituximab induction, with and without maintenance, substantially reduces the need for further treatment in patients with advanced asymptomatic follicular lymphoma. This analysis estimates the cost‐effectiveness of immediate treatment approaches in comparison to a watch and wait approach from the perspective of the UK National Health Service. A Markov decision model was developed to estimate the cost‐effectiveness of treatment strategies in patients with asymptomatic follicular lymphoma. The model was populated using effectiveness data from a systematic literature review with the key clinical data sourced from a randomised trial, in which the treatment strategies were compared. Costs were estimated using UK national sources. In comparison to watchful waiting, both rituximab strategies were found to be more effective and cost saving. In comparison to rituximab induction, the addition of rituximab maintenance marginally increased effectiveness but substantially increased costs, resulting in an incremental cost‐effectiveness ratio (ICER) of £69 406 per quality‐adjusted life year (QALY). In probabilistic sensitivity analysis, rituximab induction was found to have a 68% probability of being cost‐effective at a threshold of £20 000 per QALY. In conclusion, active treatment with rituximab induction is a cost‐effective strategy to adopt in patients with asymptomatic follicular lymphoma.